"Обеспредметившаяся предметность": наброски о материальном мире Набокова - Olga Trukhanova (eSamizdat)
Wandering in the rich gallery of interiors created by Vladimir Nabokov we can find out some interesting points that reflects on his poetics as well. In each singular description, he goes above the apparent simplicity of the domestic objects we deal with in our everyday life, transforming them in singular pieces, animated ones and bearers of memory. Starting from his early novel Queen, King, Knight Nabokov traces the path which goes beyond the usual comprehension of the things we are surrounded by and opens a new perspective where the objects can be considered as autonomous characters even capable of emotion. This paper focuses on some different approaches Nabokov uses to introduce the image of the house and the interior that in part reconnects to the XIX-century tradition (including the idea of Anti-house) and the bourgeois conception of the intimacy, the domesticity and the self-consciousness.